Battery cooling heat exchanger of Electric Vehicle - LEE, YO HAN; KIM, SE HYEON; KIM, BONG JUN (2018)
Embodiments comprise: a pair of horizontal headers; and a plurality of flat tubes having a plurality of channels connected to the pair of horizontal headers. The plurality of flat tubes are sequentially formed: a first wing unit spaced apart in the longitudinal direction of the horizontal header, and each of the plurality of flat tubes is not formed with a channel in the direction orthogonal to the longitudinal direction of the flat tube; a channel forming unit having the channel formed therein; and a second wing unit in which no channel is formed. The width of each of the first wing unit and the second wing unit is longer than a distance between the plurality of flat tubes. Therefore, a sufficient flow rate per channel can be secured as compared with a case of increasing the width of the flat tube and the number of channels. The present invention has an advantage which a heat absorbing area of the flat tube can be maximized and heat radiation performance can be maximized. 본 실시예는 한 쌍의 수평헤더와; 한 쌍의 수평헤더에 연결되는 다수의 채널이 형성된 복수개의 플랫 튜브를 포함하며, 복수개의 플랫 튜브는 수평헤더의 길이방향으로 이격되고, 복수개의 플랫 튜브 각각은 플랫 튜브의 길이방향과 직교한 방향으로 채널이 형성되지 않은 제1날개부와, 채널이 형성된 채널 형성부와, 채널이 형성되지 않는 제2날개부가 순차 형성되고, 제1날개부와 제2날개부 각각의 폭은 복수개 플랫 튜브 사이의 이격거리 보다 길게 형성되어, 플랫 튜브의 폭 및 채널의 수를 증가시키는 경우 보다, 채널 당 충분한 유량을 확보할 수 있고, 플랫 튜브의 흡열면적을 최대화될 수 있어 방열 성능을 극대화할 수 있는 이점이 있다.